Past Competition Affects Offspring Foliar Terpenoid Concentrations, Seed Traits, and Fitness in the Invasive Forb Erodium cicutarium (Geraniaceae) - Eilers, Elisabeth J.; Heger, Tina (Frontiers in Ecology and Evolution, 2019)
(1) Environmental conditions experienced in the past may lead to intraspecific differences in ecological and chemical traits of plants, which likely affect future responses to altered or new environments. Whether competition by neighbors is such a trait-shaping factor is not yet well known. We aimed to understand how the level of ancestral plant competition affects traits related to plant fitness and resource allocation, reproduction, and (phyto-)toxin accumulation in offspring, and whether a potential differentiation in these traits can be found in different geographic origins of which one belongs to the native and one to the invaded range. (2) We compared differentiation of the following traits in offspring plants of multiple populations in Erodium cicutarium (Geraniaceae): biomass, seed production, seed traits related to dispersal and germination, and concentrations of foliar mono- and sesquiterpenes. We tested the allelopatic potential of aqueous extracts of the same E. cicutarium plants on seeds of five different plant families. (3) In plants originating from populations that experienced high levels of competition, we found twice as high monoterpene concentrations. These plants also produced more biomass and a higher proportion of ripe to unripe seeds until harvesting. Seeds originating from high competition sites were shorter. Aqueous E. cicutarium leaf extracts with high terpenoid content reduced radicle length of Zea mays and radicle and hypocotyl length of E. cicutarium seedlings. (4) The results of this study provide first evidence that the surrounding vegetation may shape chemo-ecological plant traits that may be fundamental for competitive ability. Our study calls for more research testing whether competition experienced in the native range may lead to an enhanced capability of plants to establish populations and spread in a new range.